Restoration of serum estradiol and reduced incidence of miscarriage in patients with low serum estradiol during pregnancy: a retrospective cohort study using a multifactorial protocol including DHEA - Boyle, Phil; Andralojc, Karolina; van der Velden, Susanne; Najmabadi, Shahpar; de Groot, Theun; Turczynski, Craig; Stanford, Joseph B. (Frontiers in Reproductive Health, 2024)
Background Low serum estradiol in early pregnancy is associated with an elevated risk of miscarriage. We sought to determine whether efforts to restore low blood estradiol via estradiol or dehydroepiandrosterone (DHEA) supplementation would reduce the risk of miscarriage as part of a multifactorial symptom-based treatment protocol. Methods This retrospective cohort study included women with low serum estradiol levels in early pregnancy, defined as ≤50% of reference levels by gestational age. Estradiol or DHEA were administered orally, and the primary outcome measure was serum estradiol level, in reference to gestational age. The secondary outcome measures included miscarriage, birth weight, and gestational age at birth. Results We found no significant effect of estradiol supplementation on serum estradiol levels referenced to gestational age, while DHEA supplementation strongly increased estradiol levels. For pregnancies with low estradiol, the miscarriage rate in the non-supplemented group was 45.5%, while miscarriage rate in the estradiol and DHEA supplemented groups were 21.2% (p = 0.067) and 17.5% (p = 0.038), respectively. Birth weight, size, gestational age, and preterm deliveries were not significantly different. No sexual abnormalities were reported in children (n = 29) of DHEA-supplemented patients after 5–7 years follow-up. Conclusions In conclusion, DHEA supplementation restored serum estradiol levels, and when included in the treatment protocol, there was a statistically significant reduction in miscarriage.